Daya Tarik Iklan Terhadap Keputusan Pembelian - Widyana, Noor Aisffa; Eldine, Achyar; Muniroh, Leny (Manager : Jurnal Ilmu Manajemen, 2019)
Ria Busana is a business partnership in the field of fashion that has been in the field since 1999. Dealing with the economic development and business competition situation is growing rapidly, then the various efforts made by Ria Busana Group in order to assist consumers in decision making. In understanding the consumer, the company is expected to provide a positive perception to consumers, in order to create consumer loyalty in terms of shopping in Ria Busana. One of the marketing concepts that can build a positive perception in the minds of consumers is through the activity of advertising attractiveness, it is an activity to persuade consumers to buy products that are being sold and can be used as a reference marketers to predict consumer behavior in the future in the form of repeat action. The purpose of this study is to determine the effect of advertising attractiveness of purchasing decision on Ria Busana Departement Store. In this study data is processed quantitative data, the data used is secondary data company. The analysis method used is simple linear regression analysis, correlation analysis, and hypothesis test, while data processing using SPSS 18.0 for windows.